2022-VA-996-ESGO Ten steps robotic intensive staging for early-stage ovarian cancer. (20th October 2022) - Foresta, Aniello; Oliva, Riccardo; Certelli, Camilla; Biscione, Antonella; Rosati, Andrea; Loverro, Matteo; Scambia, Giovanni; Fagotti, Anna; Gallotta, Valerio
Abstract : Introduction/Background: One-third of the patients with ovarian cancer (OC) is diagnosed with FIGO stage I-II, and their five-year survival is up to 90% [1, 2]. Adequate treatment of early ovarian cancer (EOC) depends on the correct stage of the patient [3, 4]. The feasibility and safety of minimally invasive surgery (MIS) for EOC is known and can be offered to selected patients [5]. No relevant differences between robotic and laparoscopic approaches for EOC staging are described in Literature [6]. Methodology: We report the case of a 54 years-old patient diagnosed with an 81 mm adnexal mass. DaVinci robotic system was used to perform surgery with four 8 mm trocars along the transverse umbilical line, and 10 mm trocar in Palmer's point. The instruments we used were ProGrasp Forceps, fenestrated bipolar, and monopolar curved scissors. Here we aim to standardize the robotic technique for EOC staging in ten steps. Results: We have identified ten key steps to perform this procedure safely and effectively: Access to pelvic retroperitoneum; Identification of the ureter with development of pararectal and paravesical spaces; Closure of the uterine artery and section of ovarian pedicles and mobilization of adnexal mass with no-touch isolation technique; Development of rectovaginal and vescico-vaginal septum; Endobag extraction of surgical specimen; Access to lumbo-aortic retroperitoneum; Infiltration of the ovarian pedicle with indocyanine green then visualization and dissection of sentinel lymph node (LN); dissection of paracaval LN; dissection of inframesenteric LN; dissection of supramesenteric LN. Surgical time was 180 min and blood loss was 100cc without intraoperative complications. The patient was discharged on the 4th postoperative day without complications. Histology revealed a FIGO Stage IIA G3 serous endometrioid ovarian carcinoma. Conclusion: Robotic staging of EOC in ten steps is a safe and feasible technique that must be performed by an experienced oncological surgeon in referral centers.